Pengaruh Komitmen Organisasi dan Kepuasan Kerja Terhadap Kinerja Karyawan Tetap PT X Gresik - Taufiqurrahman, Moh.; Rizqi, Maulidyah Amalina; Saepuloh, Asep (Jurnal Mahasiswa Manajemen, 2025)
Background – The performance of employees of PT. X Gresik in 2021 to 2023 the number of employees who obtained excellent performance has decreased while employees with less performance has increased. With the increase in underperforming employees every year and the number of employees who perform quite a lot, of course, it can be an obstacle to achieving company goals. Objective – This research aims to determine the effect of organizational commitment and job satisfaction on the performance of permanent employees of PT. X Gresik. Design / Methodology / Approach – This research uses a quantitative approach with a sample of 57 respondents using purposive sampling technique. Data collection techniques by distributing questionnaires and data analysis techniques using descriptive statistics and multiple linear regression analysis. Findings – The results showed that organizational commitment and job satisfaction partially had a positive and significant effect on the performance of permanent employees of PT. X Gresik. Research Implication – This research can be used as a reference for PT. X Gresik to encourage better employee performance by paying attention to factors that can increase employee commitment and satisfaction. Limitations – This research has limitations only in a relatively small sample size, so it is considered less representative.